A comparison of fatigue strength sensitivity to defects for materials manufactured by AM or traditional processes. (January 2017) - Beretta, S.; Romano, S.
Highlights: The scatter of fatigue strength for AM materials is reduced if data are correlated to the defect size at failure origin. Δ σ w for AlSi10Mg and Ti6Al4V obtained by AM are similar to the properties for traditional processes. Δ K th for small cracks and Δ σ w show a significant increase, after HT or HIP, respect to the AB condition. Abstract: The fatigue behavior of metallic materials fabricated via additive manufacturing processes is currently not well understood and it has been the subject of many experimental investigations in recent years. In this paper we carried out a literature review about the fatigue strength of additively manufactured AlSi10Mg and Ti6Al4V, especially in terms of sensitivity to defects and inhomogeneities. The analysis shows that fatigue properties and key variables (heat treatment, defect size) are very similar to the ones of parts obtained with traditional manufacturing processes. These results confirm that defect tolerant design concepts can be adopted also for AM components.